Studi Karakteristik Transformator Daya Listrik dengan Multisim 12.0 - Nahdia Rupawanti BR (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2018)
Transformer has an important role in the provision of electrical energy in power systems, especially for electrical distribution. Transformer change electrical energy into electrical energy in certain capacity has function and characteristics. As one of electrical machine, transformer has loss load, capacity and efficiency. Multisim 12.0 simulation appearance the transformer can be presented.